Rural Licensed Tobacco Merchants' Smoking Status and the Sale of Tobacco to Youth - Jeanine E Gangeness; Loretta J. Heuer; Tracy Evanson (Rural Nurse Organization; Binghamton University, 2012)
The purpose of this study was to compare the sale of tobacco to youth between smoking and nonsmoking merchants in a rural county. Licensed tobacco merchants were mailed surveys regarding their personal smoking status, and the returned surveys (75.9 %, N=44) were matched with tobacco compliance results which indicated if the business sold tobacco to youth during a county compliance check. Merchants who smoked tended to sell tobacco products to youth more often than those who did not smoke chi-square (2, n=41) 6.66, p=0.036. This finding suggests the need to focus on smoking status of merchants as a prevention strategy for youth tobacco use.